Vertical Market Power in Interconnected Natural Gas and Electricity Markets - Levi Marks; Charles F. Mason; Kristina Mohlin; Matthew Zaragoza-Watkins (Center for Economic Studies and ifo Institute (CESifo), 2017)
New England is at the leading edge of an energy transition in which natural gas is playing an increasingly important role in the US electricity generation mix. In recent years, the region's wholesale natural gas and electricity markets have experienced severe, simultaneous price spikes. While frequently attributed to limited pipeline capacity serving the region, we demonstrate that such price spikes have been exacerbated by some gas distribution firms scheduling deliveries without actually owing gas. This behavior blocks other firms from utilizing pipeline capacity, which artificially limits gas supply to the region and drives up gas and electricity prices. The firms observed to withhold pipeline capacity also own non-gas electricity generation assets in New England that benefit from their gas-fired competitors paying higher fuel input costs. We estimate that capacity withholding increased average gas and electricity prices by 38% and 20%, respectively, over the three-year period we study. As a result, customers paid 3.6 billion more for electricity. While the studied behavior may have been within the firms' contractual rights, the significant impacts in both the gas and electricity markets show the need to consider improvements to market design and regulation as these two energy markets become increasingly interlinked.
Keywords: D04; D40; 330; vertical relations; pipelines; electricity markets